Volatility co-movement and the great moderation: An empirical analysis - Haroon Mumtaz; Konstantinos Theodoridis (Queen Mary University of London, School of Economics and Finance, 2016)
We propose an extended time-varying parameter Vector Autoregression that allows for an evolving relationship between the variances of the shocks. Using this model, we show that the relationship between the conditional variance of GDP growth and the long-term interest rate has become weaker over time in the US. Similarly, the co-movement between the variance of the long-term interest rate across the US and the UK declined over the 'Great Moderation' period. In contrast, the volatility of US and UK GDP growth appears to have become increasingly correlated in the recent past.
Keywords: C15; C32; E32; 330; Vector-Autoregressions; Time-Varying parameters; Stochastic Volatility